The Oriental White-eyes hosts plaintive Cuckoo and Rusty-breasted Cuckoo - Wahyu Widodo; Eko Sulistyadi (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Widodo W, Sulistyadi E. 2019. The Oriental White-eyes hosts plaintive Cuckoo and Rusty-breasted Cuckoo. Biodiversitas 20: 2093-2100. The research aims to indicate that there is a tendency that the Oriental White-eyes Zosterops palpebrosus is used as a host for Plaintive Cuckoo Cacomantis merulinus and Rusty-breasted Cuckoo Cacomantis sepulcralis. The researches were done in the year 2009, 2014, 2016 and 2018 in some conservation forest areas in Mount Pancar Recreation Nature Park and Mount Telaga Bodas Nature Reserve (West Java), Mount Wilis forest (East Java) and Mount Merapi National Park forest (Centre Java). The explorative method was used in this research. We found the fact that, at some occurrences, young Plaintive Cuckoo and Rusty-breasted Cuckoo have been hosted and fed up by a pair of Oriental White-eyes Zosterops palpebrosus. It is new information because this occurrence has never been reported before. That research, however, needs to be continued for further information. Among other things, the research is started with the presence of the Oriental White-eyes’ nest and the strategy of Plaintive Cuckoo and Rusty-breasted Cuckoo to place its egg into the nest of Oriental White-eyes. This research implicates to remind the management authority to maintain the population of remaining songbirds either in conservation areas or in non-conservation areas, as well as their buffer zones.